2011
DOI: 10.1056/nejmoa1010331
|View full text |Cite
|
Sign up to set email alerts
|

Oil-in-Water Emulsion Adjuvant with Influenza Vaccine in Young Children

Abstract: Influenza vaccine with the MF59 adjuvant is efficacious against PCR-confirmed influenza in infants and young children. (Funded by Novartis Vaccines and Diagnostics; ClinicalTrials.gov number, NCT00644059.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
215
1
7

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 292 publications
(229 citation statements)
references
References 36 publications
5
215
1
7
Order By: Relevance
“…Of the 4,372 studies initially identified (Figure), 18 RCTs [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], 14 non-randomised clinical trials [40][41][42][43][44][45][46][47][48][49][50][51][52][53], and six observational studies [54][55][56][57][58][59] were eligible for inclusion. The clinical trial registry search yielded 12 additional relevant studies (five RCTs and seven nonrandomised trials).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 4,372 studies initially identified (Figure), 18 RCTs [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], 14 non-randomised clinical trials [40][41][42][43][44][45][46][47][48][49][50][51][52][53], and six observational studies [54][55][56][57][58][59] were eligible for inclusion. The clinical trial registry search yielded 12 additional relevant studies (five RCTs and seven nonrandomised trials).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple study designs were encountered in terms of comparison groups; for non-adjuvanted TIV, comparison with placebo was only found in one study [33]. Five studies examined adjuvanted vaccines (MF59 or virosomal adjuvant) in at least one study arm [30,31,34,35,39].…”
Section: Characteristics Of Randomised Controlled Trialsmentioning
confidence: 99%
See 3 more Smart Citations